Novel human-derived EML4-ALK fusion cell lines identify ribonucleotide reductase RRM2 as a target of activated ALK in NSCLC. (September 2022) - Bokhari, A.A.; Lai, W-Y.; Le, A.T.; Gabre, J.L.; Chuang, T-P.; Fransson, S.; Bergman, B.; Djos, A.; Chen, N.; Martinsson, T.; Van den Eynden, J.; Doebele, R.C.; et al.
Highlights: EML4-ALK patient derived cell lines showed differential sensitivity towards ALK TKIs. WGS and RNA-seq analyses identified several common genetic lesions such as TP53 and CDKN2A/B. The RRM2 gene showed an overall response to ALK TKI treatment and is a downstream target of EML4-ALK fusions. 3-AP showed mild synergy with lorlatinib in EML4-ALK patient derived cell lines. Abstract: Introduction: Echinoderm microtubule-associated protein-like 4 (EML4)-Anaplastic Lymphoma Kinase (ALK) rearrangements occur in 3% to 7% of lung adenocarcinomas and are targets for treatment with tyrosine kinase inhibitors (TKIs). Here we have developed three novel EML4-ALK-positive patient–derived Non-Small-Cell-Lung-Cancer (NSCLC) cancer cell lines, CUTO8 (variant 1), CUTO9 (variant 1) and CUTO29 (variant 3) and included a fourth ALK-positive cell line YU1077 (variant 3) to study ALK-positive signaling and responses. Variants 1 and 3 are the most common EML4-ALK variants expressed in ALK-positive NSCLC, and currently cell lines representing these EML4-ALK variants are limited. Materials and methods: Resazurin assay was performed to evaluate cell viability. Protein levels were determined using western blotting. RNA sequencing was performed in all four cell lines to identify differentially expressed genes. Whole-genome sequencing was performed to determine the presence of EML4-ALK fusion and ALK tyrosine kinase inhibitor resistance mutations. Results: In this study, we have confirmed expression of the corresponding ALK fusion protein and assessed their sensitivity to a range of ALK tyrosine kinase inhibitors. These patient derived cell lines exhibit differential sensitivity to lorlatinib, brigatinib and alectinib, with EML4-ALK variant 3 containing cell lines exhibiting increased sensitivity to lorlatinib and brigatinib as compared to alectinib. These cell lines were further characterized by whole genome sequencing and RNA-seq analysis that identified the ribonucleotide reductase regulatory subunit 2 (RRM2) as a downstream and potential therapeutic target in ALK-positive NSCLC. Conclusion: We provide a characterization of four novel EML4-ALK-positive NSCLC cell lines, highlighting genomic heterogeneity and differential responses to ALK TKI treatment. The RNA-Seq characterization of ALK-positive NSCLC CUTO8, CUTO9, CUTO29 and YU1077 cell lines reported here, has been compiled in an interactive ShinyApp resource for public data exploration (https://ccgg.ugent.be/shiny/nsclc_rrm2_2022/ ).